Rancang Bangun Sistem Penggajian Pekerja Lapangan pada Perusahaan Kontruksi Denpasar, Bali: Rancang Bangun Sistem Penggajian Pekerja Lapangan pada Perusahaan Kontruksi Denpasar, Bali - Apriliyanti, Andini; Prasetya, Noven Indra (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2023)
The Denpasar, Bali Construction Company is engaged in the construction sector whose work is focused on field work. This company is a subsidiary of Company X. One of the human resources in a construction company is field workers. The company has a payroll system to provide salaries to field workers. However, in the Company there is a payroll calculation system that is fairly manual with manual recording and bypassing payroll rules, so it takes a long time. Therefore, a payroll system for field workers was created to facilitate field supervisors in calculating workers' salaries. The development method used is the waterfall because it is a systematic process so as to minimize errors, testing to ensure there are errors in a system. The results of testing the entire system are successful with a 100% percentage, can make it easier for field supervisors to calculate salaries, the finance department can view payroll reports and download, and make it easier for workers to take attendance and get payslips.